Acute-on-chronic hepatitis. A case report of autoimmune hepatitis/primary sclerosing cholangitis/ulcerative colitis overlap syndrome in a 15-year-old patient - Nalepa, Aneta; Woźniak, Małgorzata; Cielecka-Kuszyk, Joanna; Stefanowicz, Marek; Jankowska, Irena; Dądalski, Maciej; Pawłowska, Joanna (Clinical and Experimental Hepatology, 2017)
Acute-on-chronic liver failure (ACLF) is a disease in which a rapid deterioration of liver function occurs in patients with chronic liver disease, and is usually associated with a precipitating event. We present the case of a boy with autoimmune hepatitis/primary sclerosing cholangitis/ulcerative colitis (AIH/PSC/UC) overlap syndrome, in whom liver function was stable for 4.5 years of treatment. At 15 years of age the patient was hospitalized due to a deterioration of his general condition, severe abdominal pain, diarrhoea, vomiting and weight loss. There was also a rapid deterioration of liver function and a deterioration of renal function. Despite a wide spectrum of diagnostic examinations, no precipitating agent was found. After two episodes of massive bleeding from the gastrointestinal tract, the patient was transferred to the intensive care unit. The patient underwent a successful liver transplantation. ACLF can cause irreversible liver failure with a high mortality rate, which calls for liver transplantation.